Application Of The Problem Based Learning Model On Salt Hydrolysis Materials To Improve Science Process Skills And Metacognition Awareness Of Class XI MIPA Students At SMA - Ismail, Ismail; Walanda, Daud K.; Ratman, Ratman (FKIP Universitas Palangka Raya, 2024)
This study aims to determine the effect of the problem-based learning model on science process skills and metacognitive awareness of class XI MIPA students at SMA Negeri 1 Dampal Selatan. This type of research is quasi-experimental by using the Pretest-Posttest control group design. The study population was (N = 129) students of class XI MIPA SMA Negeri 1 Dampal Selatan. The sampling technique is simple random sampling. Class XI MIPA 1 (n = 32) students as the experimental class and class XI MIPA 4 (n = 32) students as the control class. The research data was collected by using an essay test to measure science process skills and questionnaires to measure the metacognitive awareness of students on the salt hydrolysis materials. Data were analyzed descriptively with the statistic application. The science process skills of students with the problem-based learning implementation model had (M = 71.84, SD = 7.956) with an effect size value of 8.92 while the discovery learning model had (M = 72.34, SD = 7.872) with an effect size value of 8.33. Metacognition awareness of students with problem-based learning implementation model has (M = 77.03, SD = 3,961) with an effect size value of 5.56 while the discovery learning model has (M = 77.62, SD = 2.738) with an effect size value of 6.46. Research result show that: (1) the problem-based learning model affects the science process skills of students on the salt hydrolysis materials; (2) the problem-based learning model affects the metacognitive awareness of students on the salt hydrolysis materials; (3) there is a positive relationship between science process skills and metacognitive awareness of students on the salt hydrolysis materials. Key words: Problem-based learning, science process skills, metacognition awareness